Thermal and mechanical properties of cationic guar gum/poly(acrylic acid) hydrogel membranes - Huang, Yihong; Lu, Jun; Xiao, Chaobo (Polymer degradation and stability, 2007)
Novel hydrogel membranes (coded as GA) based on cationic guar gum (CGG) and poly(acrylic acid) (PAA) were synthesized with various feed compositions. Their structure and properties were studied by Fourier transform infrared spectra, scanning electron microscopy, differential scanning calorimetry, thermogravimetric analyses and tensile tests. The structure analyses indicated that there existed strong electrostatic interaction between CGG and PAA, which resulted in uniform structure and complete miscibility between the two components. On the basis of thermogravimetric analyses, the activation energies ( E a) of the first degradation of the membranes increased from 34.5 to 77.1 kJ/mol with an increase of CGG content, while the residual ratios of the membranes increased from 7.6 to 36.1 wt% at 600 °C. This indicated an elevated thermal stability of PAA-based materials through an introduction of CGG. The tensile tests exhibited the mechanical properties of the membranes were improved with an increase of CGG content, and the maximum value of 41.1 MPa was reached.